Kajian Mikrobiologis Daging Ayam Giling yang Dijual di Supermarket Wilayah Jatinangor - Helda Rahayu Novianti; Eulis Tanti Marlina; Deden Zamzam Badruzzaman (Jurnal Teknologi Hasil Peternakan, 2021)
Chicken is one of the animal protein sources utilized to fulfill humans nutritional needs. Chicken is prone to be damaged and susceptible to be contaminated by pathogenic bacterial because chicken contains high nutrition. Ground meat is one of the livestock food production processed by meat-cutting and frequently sold in supermarkets. This research aims to seek the quality of microbial in chicken sold in supermarkets located in Jatinangor region. Specifically, this study attempts to ascertain the amount of bacterial and Staphylococcus aureus contained in chicken. The sampling method is carried out by simple random sampling in which the chickens are obtained from two different supermarkets in Jatinangor region. Furthermore, the calculation is carried out by using Total Plate Count (TPC) and the result is analyzed statistically by the descriptive method. The result shows that the average number of bacteria in Supermarket A is 5,43 x 10⁷ CFU/g, while in Supermarket B is 4,64 x 10⁷ CFU/g. Correspondingly, the amount of Staphylococcus aureus in Supermarket A is 7,2 x 10⁴ CFU/g and in Supermarket B is  2,9 x 10⁴ CFU/g. The number of bacterial and Staphylococcus aureus in ground chicken in both supermarkets exceeds the maximum number of microbial contamination limitations that have been determined by SNI in 2009 No.7388 which are 1 x 10⁶ CFU/g and 1 x 10 ² CFU/g.